Traditionalism and Modernism in Indonesian Islam: Dynamics of Muslim Identity Construction - Ardianto, Firdaus; M, Mukhlis; Zulhandra, Zulhandra; Lahmi, Ahmad (Ahlussunnah: Journal of Islamic Education, 2025)
This study examines the construction of Muslim identity in Indonesian Islam by analyzing the historical and socioreligious dynamics between traditionalist and modernist Islamic orientations. The research employs a qualitative method with content analysis, drawing on classical and contemporary scholarly works, historical documents, and religious discourses related to Islamic movements in Indonesia. Data were analyzed through thematic and discourse analysis to identify patterns of religious authority, interpretation, and social practice. The findings indicate that traditionalist Islam in Indonesia is characterized by strong adherence to local traditions, Sufistic practices, Shafi‘i jurisprudence, and reliance on religious authority figures, particularly within rural communities. In contrast, modernist Islam emphasizes rational interpretation, scriptural purification (tajdid), rejection of blind taqlid, and the integration of Islamic values with modern education, social institutions, and organizational activism, as represented by movements such as Muhammadiyah, Persis, and Al-Irsyad. These orientations produce distinct yet interacting forms of Muslim identity shaped by historical experiences of colonialism, modernization, and global Islamic reformism. This study implies that the coexistence and contestation between traditionalist and modernist Islam constitute a foundational element of Indonesian Muslim identity. Understanding this dynamic contributes to the discourse on religious moderation, social transformation, and the sociology of Islam in plural societies.